The Innovative Self-Sensing Strain Sensor for Asphalt Pavement Structure: Substitutability and Synergy Effects of Graphene Platelets With Carbon Nanotubes in Epoxy Composites - Xin, Xue; Luan, Xuehao; Su, Linping; Ma, Chuanyi; Liang, Ming; Ding, Ximao; Yao, Zhanyong (Frontiers in Materials, 2022)
Situ sensors with high accuracy, long durability and high survival rate are crucial for the health monitoring of asphalt pavement. Due to the harsh environment in construction period and service life, the monitoring components which can be buried synchronously with the construction period of the road surface become a difficult problem to be solved urgently. The development of functional composites sheds a new insight for pavement strain detection with remarkable self-sensing behavior. In this paper, the substitutability and synergy effect of graphene platelets with carbon nanotubes and effect of CNTs types with different specific surface areas in epoxy composites to the morphological, electrical, mechanical properties and strain-electrical resistance response peculiarity of composites were evaluated. The performance of developed composites sensor with epoxy encapsulation was investigated through laboratory experiments. The morphologies showed that CNTs-GNP hybrids in composites present better dispersion state because of the size effect and synergetic effect whereas the pure CNTs prone to entangle with each other. Composites with CNT(SSA500) display most amounts of conductive units in same dosage. CNTs and GNP can strengthen the elastic modulus of epoxy matrix with basically same as that of asphalt mixture within the range of 1100 to 1500 MPa. At last, Laboratory experiments have proved the promising prospect for CNTs-GNP/epoxy composites serving as the strain sensor. The developed composites-base strain sensor can provide a new prospect for asphalt pavement monitoring.